Menelisik Nilai- Nilai dan Implementasi Pendidikan Karakter Tradisi Kenduri Sko Suku Kerinci Serta Relevansinya Dalam Pengajaran Muatan Lokal di SMP - Vornika, Megi; Pitri, Nandia (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2024)
This study aims to examine the character values in the Kenduri Sko tradition of the Kerinci Tribe and analyze its implementation in teaching local content in junior high schools. Kenduri Sko tradition, as one of the local cultural heritages, is rich in values such as gotong royong, independence, togetherness, and religiosity, which are relevant in character education. This study used a qualitative approach with the methods of participatory observation, in-depth interviews, and document analysis. The results showed that the values of Kenduri Sko have strong relevance to the Pancasila Learner Profile in the Merdeka Curriculum, especially in the aspects of gotong royong, independence, and global diversity. The implementation of these values in Local Content teaching is carried out through project-based learning methods and reflective activities, which involve students directly in understanding and applying these values. The novelty of this research lies in integrating the values of Kenduri Sko tradition into formal teaching in junior high school, which has not been studied much before. This research makes an important contribution in developing local wisdom-based character education and offers an implementation model that can be applied in the context of education in other areas rich in local culture.